Livestock production in the Sahel: Development constraints and proposed solutions - Diallo, A.K.; Cisse, M.I.; Hiernaux, Pierre H.Y.; Blench, Roger (International Livestock Centre for Africa, 1986)
A summary of the final report of the ILCA Mali team covering the years 1982-1985. Presents research findings on ecology & pasture, animal health & production, and socio economics & intervention monitoring. Ends with proposed solutions and recommendations for future work.